The organization of the territory of the landscape reserve of local importance «Tarutyns’kyj steppe» - Олійник, Валентина (Human Geography Journal, 2020)
Protection of the natural environment, rational use of natural resources, ensuring environmental safety of human life are an essential condition for sustainable economic and social development of Ukraine. The growth of human influence on the environment includes large-scale and multi-faceted processes that generally contribute to the development of the country’s economy, but at the same time negatively affect the environment, in particular, this is reflected in its pollution, reduced soil fertility, and transformation of landscape complexes. In modern conditions of land use, it is important to create monitoring systems that will allow to state, analyze and predict phenomena in natural systems. The current ecological state of the environment of the Odessa region should be stabilized, and environmental protection measures should be aimed at improving the level of socio-economic development of the region. However, an important issue is the establishment of boundaries of objects of the nature reserve Fund. The presented work contains a practical orientation and based on legislative acts of the country. This study contains an analysis of legal acts, technical justification an explication of land within the landscape reserve "Tarutynskyj steppe" was carried out, which made it possible to determine the main provisions for optimizing the structure of land and forming highly productive, environmentally sustainable agricultural landscapes, and became the basis for the Regulation on the landscape reserve of local significance "Tarutyns’kyj steppe", allowed to give basic recommendations for effective and balanced development of the object. The regime of protection of the territory of the reserve should be taken into account when developing regional and other plans, in all types of design and planning documentation, as well as in construction projects of any objects that may affect the state of the Reserve.